Pageblug Jawa Kuna: Menggagas Folklor di Jawa Tengah sebagai Upaya Mitigasi Bencana Wabah Melalui Kartun Bergambar - Indriana, Fitri Nur Lita; Pangestu, Yogi Aji; Amanda, Bintang; Ranti, Anita Damar; Amaruli, Rabith Jihan (Department of History, Faculty of Humanities, Diponegoro University, 2023)
In Central Java, local wisdom in the form of folklore has long been recognized as a valuable resource for disaster mitigation strategies. However, amidst the COVID-19 pandemic, which the Javanese perceive as a pageblug (epidemic), the importance of disaster mitigation from a cultural perspective has been somewhat overlooked. Incorporating cultural values rooted in local wisdom can be a highly effective approach to disaster mitigation, particularly among the younger generation. In line with the fourth stage of the historical method, this study has delved into the experiences and reinterpreted values embedded within several folklores prevalent in Central Javanese society, such as Hantu Lampor, Bathara Kala, and Lintang Kemukus. Furthermore, the findings have been encapsulated in the form of illustrated cartoons. This medium is believed to serve as a powerful tool for internalizing the values of folklore in disaster management efforts, not only in Central Java but also in other regions more broadly.